Protein and Amino Acid Compositions of Sphenostylis stenocarpa, Sesamum indicum, Monodora myristica and Afzelia africana Seeds from Nigeria - Ojiako, O.A.; Igwe, C.U.; Agha, N.C.; Ogbuji, C.A.; Onwuliri, V.A. (Pakistan Journal of Nutrition, 2010)
Flours produced from raw, blanched and boiled seeds of Sphenostylis stenocarpa (African yam bean), Sesamum indicum (Sesame seed), Monodora myristica (Calabash nutmeg) and Afzelia africana (African oak) were evaluated for total protein and amino acid compositions. The results show that the seeds of S. indicum had the highest total protein content (24.74±0.56%) relative to those of S. stenocarpa (18.90±0.35%), M. myristica (12.83±0.40%) and A. africana (9.56±0.12%). The amino acid contents followed the pattern 0.030±0.010 mol/l for S. stenocarpa >0.025±0.005 mol/l for A. africana >0.014±0.003 mol/l for M. myristica >0.010±0.002 mol/l for S. indicum. The seeds were found to be rich in amino acids especially the essential amino acids which relative to the non-essential amino acids had high percentages of 81, 80, 77 and 70% for S. stenocarpa, M. myristica, S. indicum and A. Africana respectively. Boiling significantly (p